A village-based multidisciplinary study on factors affecting the intensity of cystic echinococcosis in an endemic region of the Tibetan plateau, China - HU, H. H. (Cambridge University Press, 2014)
We investigated and quantified the factors which may affect the prevalence of cystic echinococcosis caused by Echinococcus granulosus in Rangtang County using a multidisciplinary approach. From a previously performed field survey, epidemiological data were linked with environmental data. Altitude and land surface temperature were extracted from remote-sensing images. Cumulative logistic regression models were used to identify and quantify the potential risk factors. The multiple regression models confirmed that yaks (χ(2) = 4·0447, P = 0·0443), dogs (χ(2) = 8·3455, P = 0·0039) and altitude (χ2 = 7·6223, P = 0·0058) were positively correlated with the prevalence of cystic echinococcosis, while land surface temperature may have a negative association. The findings showed that dogs and yaks play the most important role in the transmission of cystic echinococcosis, while altitude and land surface temperature may also be involved in the transmission.